An empirical evaluation of the sea depth effects for various wave characteristics on the performance of a point absorber wave energy converter. (1st June 2017) - Alamian, Rezvan; Shafaghat, Rouzbeh; Shadloo, Mostafa Safdari; Bayani, Rasoul; Amouei, Amir Hossein
Abstract: In this paper, the effects of sea depth on the performance of a modified point absorber wave energy converter (WEC) are examined using an experimental study. For experimental evaluation of WEC, the general cubic shape is used. For obtaining the final shape of this novel WEC, 3 stages are considered including, still water depth optimization, optimization of geometrical specifications and shape optimization. The focus of this article is on the first stage. In this context, by creating waves with different amplitudes and periods, evaluation is conducted in three different still water depths. WEC oscillation in the directions of heave, surge and pitch are measured and compared. Furthermore, an appropriate scale for building a full scale WEC for operating in the Caspian Sea environment is studied and proposed. Experimental test results show that increasing the water depth causes an increment on the WEC oscillation on the directions of heave and pitch. However, this process is different in the case of surge oscillations; increasing the depth leads to a reduction in WEC oscillation. The analysis of these results shows that the use of point absorber WEC with the dominant motion of pitch in deep water can provide better conditions for energy extraction. Highlights: We examine the sea depth effects on the performance of a modified point absorber WEC in heave, surge and pitch directions. Increasing the water depth causes an increment on the WEC oscillation on the directions of heave and pitch. Increasing the depth leads to a reduction in WEC surge oscillation. The point absorber WEC with the dominant motion of pitch can perform better in deep water in order to extract energy.